Techno-economic assessment of a solar-based novel power generation system formed from a helium Brayton cycle and an organic Rankine flash cycle - Sharma, Achintya; Shukla, Anoop Kumar; Singh, Onkar; Sharma, Meeta (Frontiers in Energy Research, 2024)
The essential element of human existence is energy. However, conventional energy sources are steadily running out, and it is necessary to create an energy-efficient renewable power generation system. In the present work, an organic Rankine flash cycle (ORFC) was implemented in a conventional solar power tower (SPT)-helium Brayton cycle (HBC) to generate extra power, enhancing efficiency. The performance of the proposed SPT-based power generation system (SPT-HBC-ORFC) was analyzed based on thermodynamic and economic aspects using computational techniques through engineering equation solver software. The results revealed that the proposed power plant’s energy efficiency, exergy efficiency, power output, and total cost rate were 33.68%, 33.70%, 33.69%, and 15.47%, respectively, higher than those of a conventional SPT-HBC system at the given conditions. With 39% of all exergy destruction, heliostats are the source of the greatest exergy destruction. Parametric analysis reveals that solar subsection parameters had a larger effect on the performance of the proposed power plant. Comparisons with previous studies show that the present power generation system is more efficient than the SPT-based supercritical CO2 Brayton and Rankine cycles.